2021
DOI: 10.31349/revmexfis.67.263
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of electrical conductivity of SnS thin film of 0.2 < t ≤ 0.4 μm thicknes for field effect transistor application

Abstract: This study is focused on the investigation of SnS thin film for transistor application. Electron trap which is associated with grain boundary effect affects the electrical conductivity of SnS semiconductor thin film thereby militating the attainment of the threshold voltage required for transistor operation. Grain size and grain boundary is a function of a semiconductor’s thickness. SnS semiconductor thin films of 0.20, 0.25, 0.30, 0.35, 0.40 μm were deposited using aerosol assisted chemical vapour deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…As a result, these defects act as dispersion centers, increasing the resistivity of the films. These findings are consistent with those reported by Daniel et al [23].…”
Section: Electrical Studiessupporting
confidence: 94%
“…As a result, these defects act as dispersion centers, increasing the resistivity of the films. These findings are consistent with those reported by Daniel et al [23].…”
Section: Electrical Studiessupporting
confidence: 94%
“…For example, in [37], for the Cd 1−x Zn x S films, the dependence of the electrical conductivity on the grain size was shown, and it was found that the electrical conductivity had a maximum for the film with a grain size of about 36.445 nm (5 × 10 -10 (Ω•m) -1 ). The electrical conductivity of SnS films with crystallites of 55.05 nm is 2.364 × 10 -7 (Ω•cm) −1 (δ = 3.30 × 10 14 m -2 and ε = 2.31 × 10 -3 ) [38].…”
Section: X-ray Analysis Of Thin Filmsmentioning
confidence: 99%
“…The crystallite size (D) of the CNTSSe films was determined from the Scherrer equations as follows [37,38]:…”
Section: X-ray Analysis Of Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation